Interaksi antar Aktor dalam Penyelenggaraan Asian Games 2018: Bentuk Wisata Olahraga Berkelanjutan melalui Kerja Sama Multipihak - Fauzie, Hanna; Virgianita, Asra (Review of International Relations, 2024)
This research analyzes the multi-stakeholder collaboration that occurred during the organization of the tourism sporting event, Asian Games 2018, in Indonesia, as part of sustainable tourism implementation. The study adopts the transactional collaboration framework developed by Visseren-Hamakers et. al. (2007), emphasizing the significance of understanding dynamic interactions among government, private sector, and society in achieving goals, particularly within the context of sustainable development. Data for the study were derived from interviews with relevant stakeholders and the analysis of pertinent document studies. The findings reveal that the primary challenges in multi-stakeholder collaboration involve imbalances and hierarchies in interactions between international and national actors. The Olympic Council of Asia (OCA) assumes a dominant role with greater resources, yet neglects the aspect of sustainable tourism in the execution of Asian Games 2018. Business groups prioritize profits over sustainable development. The role of civil society organizations (CSOs) in decision-making related to the Asian Games is limited, underscoring the research's implications on the necessity for more equitable engagement between international and national actors, and the reinforcement of CSOs' role in driving sustainable tourism implementation in sporting events.